2021
DOI: 10.1111/ijcp.14052
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 and its effect on the provision of ophthalmic care in the United Kingdom

Abstract: The first quarter of 2020 gave light to a novel virus, Coronavirus 2019 , causing a pandemic of unbridled proportions. The National Health Service in the United Kingdom issued guidance to ensure that capacity was increased in acute medical settings, to prepare for the surge of COVID-19 cases. The Royal College of Ophthalmologists followed suit with guidance on the curtailment of all elective activity, aimed at protecting both patients and staff. Ophthalmology is one of the busiest outpatient specialities, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…At the same time, new working methods should be considered, such as simplifying services, reducing patient backlog, and telemedicine. 77 …”
Section: Reducing the Risk Of Covid-19 In The Ophthalmology Departmentmentioning
confidence: 99%
“…At the same time, new working methods should be considered, such as simplifying services, reducing patient backlog, and telemedicine. 77 …”
Section: Reducing the Risk Of Covid-19 In The Ophthalmology Departmentmentioning
confidence: 99%
“…The Royal College of Ophthalmologists issued guidance on Ophthalmology services during the pandemic. This guidance weighed the risk of patients experiencing Covid‐19 by attending hospital dates against the risk of harm by delaying treatment [ 6 ].…”
Section: Lockdown and Ophthalmology Carementioning
confidence: 99%
“…The results showed that there was a backlog and significant delay in the elective procedures and operations in the eye care units. Additionally, the protocols limiting the number of patients per day and the triage Conjunctival congestion 5% [10,28] system to screen any possible Covid-19 patients caused a delay in the eye service provided [6]. Thus, the health authorities tried to overcome these obstacles and manage the lockdown effect.…”
Section: Lockdown and Ophthalmology Carementioning
confidence: 99%
See 1 more Smart Citation